Macroeconomic determinants of credit risks: Evidence from high-income countries - Laxmi Koju; Ram Koju; Shouyang Wang (European Journal of Management and Business Economics (EJM&BE), 2020)
Purpose The purpose of this paper is to empirically assess the significant indicators of macroeconomic environment that influence credit risk in high-income countries. Design/methodology/approach The study employs the system generalized method of moments estimator to avoid the dynamic panel bias and endogeneity issues. Different indices of economic growth are used in each model in order to find the most significant proxy of the economic cycle that influences problem loans. The analysis is carried out using a sample of 49 developed countries covering a 16-year period (2000-2015). Findings The overall empirical results highlight that the development of industrial sectors and exports are the main drivers of loan performance in high-income countries. The findings specifically recommend adopting an expansionary fiscal policy to boost per capita income and potential productivity for the safety of the banking system. Practical implications The findings have direct practical applicability for stabilizing the financial system. The study recommends the government to increase the productivity of export-oriented industries in order to boost employment and increase the payment obligations of individuals and business firms. More importantly, it highlights the essentiality of perfect economic policy to control default risks. Originality/value To the best of the authors' knowledge, this is the first empirical study that compares the relative effect of three alternative proxies of the economic cycle on credit risk and identifies the most significant proxy. The current study also empirically shows that industrial development could be one of the crucial factors to improve financial health in developed countries.
Keywords: E44; G21; 650; Financial stability; Trade openness; Industrial policy; National expenditure; Non-performing loan; Per capita income